Synthesis and characterization of cobalt phthalocyanine/MCM-41 and its photocatalytic activity on methyl orange under visible light. Issue 52 (7th November 2016) - Wang, Dejun; Guo, Rui; Wang, Shuaijun; Liu, Fang; Wang, Yongqiang; Zhao, Chaocheng
Abstract: The photocatalytic activity of cobalt phthalocyanine (CoPc) immobilized onto MCM-41 was investigated for decomposition of methyl orange in aqueous solutions. The morphology and structure of the catalyst were analyzed by diffuse reflectance ultraviolet-visible (DR UV–vis), X-ray diffraction, Fourier transform infrared, and scanning electron microscopy (SEM). Photocatalytic efficiency of the prepared catalyst for degradation of methyl orange was tested under illumination of visible light. The photodegradation process is completed within 2 h using a dose of 0.04 g/L of the catalyst in the 0.05 g/L of methyl orange solution under Xenon lamp, and the removal rate was 98.3%. The obtained results revealed that the photocatalyst was very active in degradation of methyl orange.